EU Energy Innovation Policy Towards 2050. - Glachant, Jean-Michel (European energy studies., 2012)
What is the European energy strategy for 2050? How different is it from the 2020 energy strategy? What are the technology options? What are the policy options? This volume discusses the European ""2050 Energy Roadmap to a Low Carbon Economy: Energy Policy & Innovation."" The book represents the outcome of the Third Academic Roundtable of the Loyola de Palacio Chair at the European University Institute, held in Florence in May 2011. It introduces the most recent thinking regarding the European transition towards a low carbon future. The views presented include those of experts of the European C.